The portrayal of psychiatry in American and Brazilian cinema (Archives of Clinical Psychiatry, 2010)
INTRODUCTION: As cinema has an easy accessibility, it seems to influence society's image of psychiatry. OBJECTIVES: To accomplish a systematic review of the literature about the portrayal of psychiatry in American and Brazilian films. METHODS: With no date limits, we searched the databases: LILACS, MedLine, PsychLit, PsycINFO and SciELO. We used the following terms in English and, in LILACS and SciELO, their equivalent in Portuguese: "psychiatry" AND/OR "motion pictures as topic". A manual search was also done. Accurate inclusion and exclusion criteria were stipulated. RESULTS: Twenty indexed articles and two books. In American cinema, the data have allowed to identify a constant stereotyped portrayal of different aspects of psychiatry, its ambivalent image and five distinct phases of its depiction. In Brazilian cinema, the few studies about the image of psychiatry have focused on "The retaken" phase. The majority of its films have showed some psychopathological content. DISCUSSION: As almost all articles have been descriptive, it was difficult to establish a comparison among them. However, it was possible to draw a parallel between US films and Brazilian ones. CONCLUSION: The portrayal of psychiatry differs between American and Brazilian cinema mainly because the sample of analyzed movies came from very distinct periods.